Conjunctival autograft for recurrent conjunctival granuloma - Kresentia, Stevie; Surya, Amir (International Journal of Research in Medical Sciences, 2022)
Pyogenic granuloma is a benign vascular tumour that can arise from several reasons and tends not to transform into malignant. These tumours, which are more common in young people, may also recur. Just like in this case, a 39-year-old man came with a mass on his left eyeball that had been enlarged since two weeks ago. He also had a history of surgery on his left eye one month ago. From the examination results, the visual acuity was 5/5 and a 2mm, reddish, firmed border mass on the bulbar conjunctiva at the nasal area. He was diagnosed with conjunctival granuloma and we decided to do tumour excision and also histopathology examination. The histopathology results specified a granuloma. Three weeks later, there was the same mass growth but more prominent. We decided to re-excise with a conjunctival autograft and administered ophthalmic and oral steroids to minimize the recurrence. One month after surgery, the conjunctival graft had already fused with the surrounding conjunctiva without oedema, and five months later, no new granuloma growth was seen. This method can be considered for patient’s comfort and cosmetics but still requires further research and a larger number of samples to ensure the accuracy of the data.